Model of Publishing Activities of Scientific Libraries - Zlyhostiev Serhiy (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The article highlights the peculiarities of implementing a publishing model. The aspects that indicate the importance of creating such a model are revealed. The publishing model makes it possible to take into account all the factors that may affect this process. The issue of the publishing activity model is almost not covered in the scientific literature, which is of considerable scientific interest. To effectively organize any activity, you need to set aside time and form a model of such activity. In the course of our study, we managed to investigate the peculiarities of the publishing activities of libraries and identify aspects that can be the basis for a model of publishing activities. The optimal model of publishing activity is proposed. The model is based on the analysis of scientific papers and publishing activities of national libraries and libraries of higher education institutions. By the model of publishing activity, we mean the strategy by which the preparation, production and distribution of publishing products are carried out. It is worth noting that the developed model is a valuable tool for assessing the current state of publishing activities of libraries, identifying priority areas of development and developing a strategy that will help to increase the efficiency and profitability of these activities. It is worth noting that the developed model is a valuable tool for assessing the current state of library publishing activities, identifying priority areas for development, and developing a strategy that will help increase the efficiency and profitability of these activities. In creating the model, we tried to take into account all the important aspects of library publishing activities and aspects that can improve these activities. We do not exclude the possibility that in the process of a deeper analysis of the publishing activities of libraries in certain categories, certain changes may be made to the model to adapt it to a particular library.